2012
DOI: 10.3109/10253890.2012.707709
|View full text |Cite
|
Sign up to set email alerts
|

Displacement behaviour regulates the experience of stress in men

Abstract: Behavioural coping strategies represent a key means by which people regulate their stress levels. Attention has recently focused on the potential role in coping of 'displacement behaviour' - activities such as scratching, lip biting and face touching. Increased levels of displacement behaviour are associated with feelings of anxiety and stress; however, the extent to which displacement behaviour, as a short-term behavioural response to emotionally challenging stimuli, influences the subsequent experience of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 47 publications
2
41
1
Order By: Relevance
“…The link between displacement behavior and fundamental personality traits, such as neuroticism, in healthy populations is much more rarely considered. Previously, we have shown that the rate of displacement behavior during a TSST is unrelated to trait anxiety levels in men (Mohiyeddini & Semple, 2013) and is negatively related to public self-consciousness in women (Mohiyeddini et al, 2013b). There is marked interindividual variation in displacement behavior among both normal (Bardi, Koone, Mewaldt, & O'Connor, 2011) and clinical (Troisi, Spalletta, & Pasini, 1998) populations.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The link between displacement behavior and fundamental personality traits, such as neuroticism, in healthy populations is much more rarely considered. Previously, we have shown that the rate of displacement behavior during a TSST is unrelated to trait anxiety levels in men (Mohiyeddini & Semple, 2013) and is negatively related to public self-consciousness in women (Mohiyeddini et al, 2013b). There is marked interindividual variation in displacement behavior among both normal (Bardi, Koone, Mewaldt, & O'Connor, 2011) and clinical (Troisi, Spalletta, & Pasini, 1998) populations.…”
Section: Discussionmentioning
confidence: 97%
“…It has long been established that the rate of displacement behavior increases with the experience of negative emotional states such as anxiety and stress C. Mohiyeddini et al 392 (Ekman & Friesen 1972;Mohiyeddini & Semple, 2013;Mohiyeddini, Bauer, & Semple, 2013a, 2013bTroisi, 2002). It is only relatively recently, however, that research has highlighted the importance of displacement behavior as a particularly salient variable underlying individual differences in coping with social stress.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Stereotypies and self-directed behavior may develop as coping mechanisms, and therefore individuals that perform these may experience better welfare states than those in comparable environments that lack coping strategies (Mason and Latham, 2004;Mohiyeddini and Semple, 2013). Furthermore, animals that perform stereotypies are resistant to behavioral extinction and therefore the existence of stereotypies do not necessarily indicate current welfare state (Mason and Latham, 2004;Mason, 2006).…”
mentioning
confidence: 99%